Shark bycatch of the acoupa weakfish, Cynoscion acoupa (Lacèpede, 1801), fisheries of the Amazon Shelf - Lutz, Ítalo; Pinaya, Walter Hugo Diaz; Nascimento, Mayra; Lima, Wellington; Silva, Evaldo; Nunes, Zélia; Bentes, Bianca (Frontiers in Marine Science, 2023)
In recent years, the populations of many shark species have been depleted drastically around the world. In the present study, we analyzed the shark bycatch in the monthly landing data of the acoupa weakfish (Cynoscion acoupa) gillnet fisheries of the state of Pará, on the northern coast of Brazil, between January 1995 and December 2007. Based on 4,659 landings, we estimated that a total of 1,972.50 tons of shark were taken as bycatch during the study period. The acoupa weakfish fisheries operate on the Amazon Shelf, an important fishing ground, and we analyzed the shark landings in relation to the Amazon River Discharge anomaly (ARD) and the climatic variability in the Atlantic Ocean. We applied cross-correlation, cross-wavelet, wavelet coherence, and redundancy analysis techniques to the analysis of the data time series. The shark bycatch landings peaked between 1998 and 2000, a period associated with an increase in fishing effort by the acoupa weakfish fisheries, in particular during the dry season of the Amazon basin. The cross-correlation analysis indicated that shark landings were associated with Sea Surface Temperatures (SSTs), the characteristics of the wind, and the Atlantic Multidecadal Oscillation (AMO), while the fishing effort of the acoupa weakfish fisheries was associated with the meridional wind component, the AMO, and the ARD. The cross-wavelet and coherence wavelet analyses indicated that environmental variability was linked systematically with shark landings and acoupa weakfish fishing effort. We observed a phase change in this signal between 1998 and 2000, due to a strong and persistent La Niña event. Despite the resistance from the fishing industry, development and deployment of devices designed to reduce bycatch should be incentivized in order to reduce the unintentional capture of endangered species such as sharks. The findings of the present study highlight the importance of a continuous and accurate fishery database, and the need for continuous fishery statistics to ensure adequate management practices. Adequate public fishery management policies must be implemented urgently to guarantee the survival of shark species, with the effective participation of all the actors involved in the process, including managers, researchers, and fishers.